A Model for Managing Knowledge in Dietetics: A Case Study of Hospital Tuanku Fauziah - Vellapandian, Shamili Poonmalar (2006)
The main aim of this project is to propose a model for managing knowledge in dietetics by utilizing a case study approach involving the dietetics of Hospital Tuanku Fauziah. To achive this, the knowledge that existed in the dietetics department was identified and classified into tacit and/or explicit. Then the Nonaka and Takeuchi's prominent SECI model was applied and adapted to manage the knowledge identified earlier. The whole process of this research project execution was based on the methodology adapted mainly from the Knowledge Management Life Cycle (KMSLC). The major outcome of this research are models and ways of managing knowledge which have been segregated for the three major designations of the dietetics unit which are the dieticians, catering officers and kitchen mistress. The research findings indicate that the SECI model can be applied and adapted accordingly in any environment.